Literature Review of Vehicles Routing Problems Using Metaheuristics: Prospects and Trends - Mishra C.; Manjari; Singh S.; Jauhar S.K.; Pratap S.; Pandey A.K. (My University, 2025)
The field of GA and SA has made significant progress in solving complex optimization problems, and it continues to evolve with the emergence of new algorithms. This paper focuses on providing a comprehensive overview of the research conducted in GA and SA specifically related to vehicle routing and the application of genetic algorithms and simulated annealing. The study involves a bibliometric analysis of approximately 48 papers published from 2018 onwards. These papers are classified based on relevant keywords to examine the advancements and trends in the field. Additionally, this paper discusses recent developments, identifies research gaps, and outlines future directions specifically in the context of vehicle routing and the application of genetic algorithms and simulated annealing algorithms. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.